# Answer on Trigonometry Question for Kristen Woods

Question #20813

if f(x)=x^2+3 and g(x)=3x-1

then find the following

1d. (fg)(x)

1e. fg(-1)

1f. (f/g)(x)

then find the following

1d. (fg)(x)

1e. fg(-1)

1f. (f/g)(x)

Expert's answer

1d. (fg)(x)=(x^2+3)(3x-1)=3x^3-x^2+9x-3

1e. (fg)(-1)=3(-1)^3-(-1)^2+9(-1)-3=-3-1-9-3=-16

1f. (f/g)(x)=(x^2+3)/(3x-1)

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment